Kepuasan Kerja Ditinjau Dari Work Life Balance Pada Karyawan Pt. Telkom Di Kabanjahe - Hartini, Sri; Vitan, Kelvin; Ferincia, Ferincia; Wijaya, Jessica (Jurnal Ilmiah Wahana Pendidikan, 2023)
Human resources are resources that play an important role in achieving company goals. Good human resource management will have a positive impact on the company. This research was conducted to determine the relationship between Work-Life Balance and job satisfaction among employees at PT. Telkom Kabanjahe. Work-Life Balance as an independent variable consists of three factors, namely work interference with personal life, personal life interference with work, and work personal life enhancement. Meanwhile, job satisfaction as a dependent variable is divided into five factors, namely the job itself, superiors, co-workers, promotions and salary/wages. This type of research uses quantitative methods. The data used in this research is primary data obtained from interviews and questionnaires distributed to 110 respondents as well as secondary data in the form of documents from the company. The sample collection technique used was Saturated sampling. The data analysis method used is Pearson Product Moment Correlation, using the SPSS program. The results of this research show that there is a positive relationship between Work-Life Balance and employee job satisfaction of 16.6% and the rest is influenced by other variables not examined in this research.